The Lies You Tell: Disrupting the Dominant Depiction of Black Women in Film - Josie L. Andrews; Adam McClain (Adult Education Research Conference, 2022)
Hollywood negatively depicts Black women, often minimizing or ignoring their character’s developmental milestones or self-actualization. Using Black Feminist Thought, an oppositional gaze was used to analyze their development in film.
Keywords: Black women; American film; adult development